Дослідження та програмна реалізація системи кібербезпеки для виявлення вразливостей web-застосунків - Толмачов, Юрій Петрович; Tolmachov, Yuri (ЦНТУ, 2021)
В даній випускній кваліфікаційній роботі за другим (магістерським) рівнем вищої освіти розроблено програмне забезпечення, яке призначено для системи кібербезпеки для виявлення вразливостей web-застосунків. Метою розробки є дослідження та програмна реалізація системи кібербезпеки для виявлення вразливостей web-застосунків. Об’єктом дослідження є процес кібербезпеки для виявлення вразливостей web-застосунків. Предметом дослідження є методи кібербезпеки для виявлення вразливостей web-застосунків. Методи дослідження базуються на методах теорії захисту інформації, методах математичної статистики, методах розробки програмного забезпечення. Результат роботи – програмна реалізація системи кібербезпеки для виявлення вразливостей web-застосунків. В процесі роботи над програмною моделлю виконано аналіз існуючих апаратних та програмних засобів. В повній мірі описані всі компоненти розробленого програмного забезпечення. Розроблено зручний інтерфейс користувача. Наведені інструкції по роботі з програмними засобами. Програма може використовуватися на ПЕОМ архітектури IBM PC з ОС Windows ХР/Vista/7/8/10. Програму розроблено в середовищі Java. In this final qualification work for the second (master's) level of higher education, software has been developed that is designed for the cybersecurity system to detect vulnerabilities in web applications. The purpose of the development is to research and software implementation of a cybersecurity system to identify vulnerabilities in web applications. The object of research is the process of cybersecurity to detect vulnerabilities in web applications. The subject of the study is cybersecurity methods to detect vulnerabilities in web applications. Research methods are based on methods of information security theory, methods of mathematical statistics, methods of software development. The result is a software implementation of a cybersecurity system to detect vulnerabilities in web applications. In the process of working on the software model, an analysis of existing hardware and software was performed. All components of the developed software are fully described. Developed user-friendly interface. Instructions for working with software are given. The program can be used on an IBM PC with Windows XP / Vista / 7/8/10. The program is developed in the Java environment.
Research and software implementation of a cybersecurity system to detect vulnerabilities in web applications
Keywords: комп’ютерна інженерія; вразливості; web-застосунки; computer engineering; vulnerabilities; web applications